An Investigation of the Effectiveness of Deepfake Models and Tools - Md. Saddam Hossain Mukta; Jubaer Ahmad; Mohaimenul Azam Khan Raiaan; Salekul Islam; Sami Azam; Mohammed Eunus Ali; Mirjam Jonkman (Journal of Sensor and Actuator Networks, 2023)
With the development of computer vision and deep learning technologies, rapidly expanding approaches have been introduced that allow anyone to create videos and pictures that are both phony and incredibly lifelike. The term deepfake methodology is used to describe such technologies. Face alteration can be performed both in videos and pictures with extreme realism using deepfake innovation. Deepfake recordings, the majority of them targeting politicians or celebrity personalities, have been widely disseminated online. On the other hand, different strategies have been outlined in the research to combat the issues brought up by deepfake. In this paper, we carry out a review by analyzing and comparing (1) the notable research contributions in the field of deepfake models and (2) widely used deepfake tools. We have also built two separate taxonomies for deepfake models and tools. These models and tools are also compared in terms of underlying algorithms, datasets they have used and their accuracy. A number of challenges and open issues have also been identified.